On the monoclinic distortion of β-anhydrite CaSO4 - Beaugnon, Florian; Quiligotti, Sara; Chevreux, Sylviane; Wallez, Gilles (Solid state sciences, 2020)
β-anhydrite, the stable form of CaSO4, is a common mineral and a key phase in gypsum's dehydration mechanism. An in-depth multi-scale investigation of its structure by powder X-ray diffraction revealed a very slight distortion of the crystal cell at room temperature (β = 90.092(9) °), that led to rule out the commonly admitted orthorhombic model (space group Cmcm) in favor of monoclinic C2/c subgroup. According to high-temperature XRD, the structure resumes however the orthorhombic symmetry around 400 °C. [Display omitted] •The first evidence of a lattice distortion in β-anhydrite.•A “pseudo tetragonal – pseudo orthorhombic” monoclinic symmetry.•A second-order phase transition is observed around 400 °C.